2016
DOI: 10.22246/jikm.2016.37.6.998
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Thickness of the Abdominal Wall at Abdominal Acupoints Using Ultrasonography and Analyzing Correlations with Physical Examination Values in Functional Dyspepsia Patients

Abstract: Objective. To explore the existing scientific information regarding safe needling depth of acupuncture points and the needling depth of clinical efficacy. Methods. We searched the PubMed, EMBASE, Cochrane, Allied and Complementary Medicine (AMED), The National Center for Complementary and Alternative Medicine (NCCAM), and China National Knowledge Infrastructure (CNKI) databases to identify relevant monographs and related references from 1991 to 2013. Chinese journals and theses/dissertations were hand searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
(73 reference statements)
0
1
0
1
Order By: Relevance
“…Among the 46 studies, a Korean medicine doctor led ultrasonography in 13 Evaluating the condition of joints and muscles [29] Sonograph can be more utilized than X-ray for differential diagnosis especially sensitive on the problem of effusion U Kim (2010) [30] When evaluating joint ultrasonography, Beevenom acupuncture was effects on pain, physical function and knee joint effusion U [31] For shoulder joints function and sonography, it was found that the pronation and internal version ranges are restricted indicating close relationship between mortor restriction of shoulder joints and scapular U Park (2012) [32] Intraarticular sonographic findings including cartilage thickness was correlated with extraarticular findings including PAT and a symptom of knee pain (p < 0.05) U KMD, Korean medicine doctor; MT, medical technician; NA, not applicable; PAT, Pes Anserinous tendinopathy; R, roentgenologist; TPVS, thoracic paravertebral space; U, unknown. [33] The possibility of estimating the thickness of the abdominal wall by looking at the characteristics of patients with functional dyspepsia, including the sternocostal angle. U Nam (2010) [34] Repeatability and reproducibility of the ultrasonography device system for measuring distance from CV13 to pancreas was acceptable KMD Kim (2011) [35] From the abdominal surface of Sangwan (CV13) to peritoneum in front of anterior surface of liver, 9 ㎒ linear probe and solid gel pad were acceptable KMD…”
Section: Discussionmentioning
confidence: 99%
“…Among the 46 studies, a Korean medicine doctor led ultrasonography in 13 Evaluating the condition of joints and muscles [29] Sonograph can be more utilized than X-ray for differential diagnosis especially sensitive on the problem of effusion U Kim (2010) [30] When evaluating joint ultrasonography, Beevenom acupuncture was effects on pain, physical function and knee joint effusion U [31] For shoulder joints function and sonography, it was found that the pronation and internal version ranges are restricted indicating close relationship between mortor restriction of shoulder joints and scapular U Park (2012) [32] Intraarticular sonographic findings including cartilage thickness was correlated with extraarticular findings including PAT and a symptom of knee pain (p < 0.05) U KMD, Korean medicine doctor; MT, medical technician; NA, not applicable; PAT, Pes Anserinous tendinopathy; R, roentgenologist; TPVS, thoracic paravertebral space; U, unknown. [33] The possibility of estimating the thickness of the abdominal wall by looking at the characteristics of patients with functional dyspepsia, including the sternocostal angle. U Nam (2010) [34] Repeatability and reproducibility of the ultrasonography device system for measuring distance from CV13 to pancreas was acceptable KMD Kim (2011) [35] From the abdominal surface of Sangwan (CV13) to peritoneum in front of anterior surface of liver, 9 ㎒ linear probe and solid gel pad were acceptable KMD…”
Section: Discussionmentioning
confidence: 99%
“…. 최근에는 해부용 시신에 초음파를 적용한 연구가 발표되었고 23) , 국내에서도 성인을 대상으로 초음파 및 CT 를 활용하여 연구가 이루어졌다(Table 2) [24][25][26][27] .…”
Section: 복부 경혈의 안전한 자침 깊이 관련 연구unclassified